Antimicrobial activities of Trichoderma atroviride against common bean seed-borne Macrophomina phaseolina and Rhizoctonia solani. Issue 1 (1st January 2020) - El-Benawy, Naglaa M.; Abdel-Fattah, Gamal M.; Ghoneem, Khalid M.; Shabana, Yasser M.
ABSTRACT: Common bean ( Phaseolus vulgaris L.) is the most consumed legume worldwide, with a commercial value surpassing that of all other legume crops combined. Seed-borne fungi cause at least 10% loss in common bean. Standard blotter (SB) and agar plate (AP) techniques were used to identify seed-borne fungi associated with common bean seeds. Thirty-two fungal species comprising 23 genera were detected. Among the fungal pathogens recovered, Macrophomina phaseolina and Rhizoctonia solani were predominant with a higher recovery using the AP technique than SB technique. Antagonistic activities of six Trichoderma isolates associated with healthy common bean seeds were evaluated against both pathogens, M. phaseolina and R. solani through a dual culture assay. Of them, Trichoderma isolate T22 remarkably suppressed the growth of both pathogens (72.42% and 68%, respectively), 5 days after inoculation. Both pathogens were completely overgrown by T22 mycelia, and sclerotia formation by the two pathogens was lacking compared to the control plates, after 8 days. The T22 isolate was morphologically identified as T. atroviride . The scanning electron microscopy (SEM) confirmed the mycoparasitism of T. atroviride T22 against M. phaseolina and R. solani, resulting in mycelium collapse of both pathogens. A total of nine unique volatile compounds of T. atroviride T22 filtrate were identified by GC-MS technique, representing 75.03% of the total components. Among them, 5-hydroxymethylfurfural (46.11%), and 4 H-pyran-4-one, 2, 3-dihydro-3, 5-dihydroxy-6-methyl- (15.66%) were detected as major components, while furfural (3.14%), hexadecanoic acid, 2-hydroxy-1-(hydroxymethyl) ethyl ester (2.81%), 1, 2-cyclopentanedione (2.79%), and 2-furanmethanol (2.09%) were found to be minor compounds. Our results confirmed that T. atroviride T22 can be used as an effective biocontrol agent against M. phaseolina and R. solani, which are pathogens on common beans and many other crops.